Utilizing a defective MgO layer for engineering multifunctional Co-MOF hybrid materials with tailored leaf-like and polyhedral structures for optimal electrochemical and photocatalytic activities - Mohammad Aadil; Muhammad Ali Khan; Safira Ananda Repycha; Mosab Kaseem (Nano Materials Science)
The hybridization of metal-organic framework (MOF) with inorganic layers would lead to the discovery of novel hybrid materials that can provide a compelling strategy for enhancing its photocatalytic and electrochemical response. In the present study, a highly efficient multifunctional hybrid material was developed by exploiting the defective layer formed on AZ31 Mg alloy through plasma electrolytic oxidation (PEO) as a nucleation and growth site for Co-MOF. The concentrations of the organic linker 2-Methylimidazole (2,MIm) and cobalt nitrate as a source of Co2+ ions were varied to control the growth of the obtained Co-MOF. Lower concentrations of the 2, MIm ligand favored the formation of leaf-like MOF structures through an anisotropic, two-dimensional growth, while higher concentrations led to rapid, isotropic nucleation and the creation of polyhedral Co-MOF structures. The sample characterized by polyhedral Co-MOF structures exhibited superior electrochemical stability, with the lowest corrosion current density (3.11 ​× ​10−9 A/cm2) and the highest top layer resistance (2.34 ​× ​106 ​Ω ​cm2), and demonstrated outstanding photocatalytic efficiency, achieving a remarkable 99.98 ​% degradation of methylene blue, an organic pollutant, in model wastewater. To assess the active adsorption sites of the Co-MOF, density functional theory (DFT) was utilized. This study explores the changes in morphologies of the coatings of Co-MOF with the change of solution concentration to form coatings with enhanced properties on the metallic substrate, which could establish the groundwork for the development of next-generation multifunctional frameworks with diverse applications.